Educational Model of Religious Humanist Values In Madrasah - Febriyanti Febriyanti; Handriadi Handriadi; Tamsik Udin; Suhendri Suhendri; A. Octamaya Tenri Awaru (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research set out to identify the Madrasah educational paradigm for religious humanism principles. A literature review was performed as the research methodology. It is recognised that the model of religious humanism value education in Madrasahs, namely 1) The Model of Religious humanism Values, is based on examination of many literary sources, including books, papers, and prior research. The educational system used in madrasahs is integralistic. The covert curriculum, meanwhile, contains the instructional process. The process of fostering religious humanist educational values in Madrasas has taken the form of meaningful learning (meaningfull learning); transformative learning; dialogical learning; growth towards the development of self-respect character; realisation of learning experiences; and freedom to learn (freedom to learn) human/student potential towards physical, intellectual, and moral development.